Systematic Literature Review: Team Performance and Psychological Factors Affecting Effective Collaboration in the Workplace - Aida Dwipriwanti; Yosi Mariana; F. Danardana Murwani; Ludi Wishnu Wardana (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
Effective collaboration is a strategic imperative for contemporary organizations, yet its success hinges critically on team dynamics and underlying psychological factors like Trust and Psychological Safety. The purpose of this Systematic Literature Review (SLR) was to synthesize empirical research published between 2020 and 2025 to clarify how these psychological factors influence collaboration and team performance. Following the PRISMA guidelines, a rigorous search on Google Scholar using keywords such as "team performance," "psychological factors," and "collaboration" resulted in the final inclusion of 15 articles for in-depth synthesis. Findings confirm that Trust is the most vital psychological construct, acting as a crucial mediator: it successfully transmits the positive effects of Transactional Leadership on employee performance and, conversely, mediates the detrimental effect of Toxic Leadership leading to Employee Silence. Leadership Soft Skills and Emotional Intelligence are identified as primary antecedents that build perceived trustworthiness, which, in turn, significantly reduces Turnover Intention. The review also highlights emerging contexts: trust is now influenced by Agent-Related Factors in Human-AI Teams (HATs), and unconventional factors like Corporate Comedy are found to positively contribute to Group Cohesion. However, contradictory findings regarding trust's role in Knowledge Sharing suggest a significant research gap. This SLR concludes that building psychological capital is fundamental to effective collaboration and recommends that future research utilize Structural Equation Modeling (SEM) to validate conceptual frameworks and employ mixed-methods approaches to resolve contextual conflicts within the literature.